﻿

# Frobenius method

In mathematics, the Frobenius method, named after Ferdinand Georg Frobenius, is a way to find an infinite series solution for a second-order ordinary differential equation of the form $z^2u''+p(z)zu'+q(z)u=0 \,$

in the vicinity of the regular singular point z=0. We can divide by z2 to obtain a differential equation of the form $u''+{p(z) \over z}u'+{q(z) \over z^2}u = 0$

which will not be solvable with regular power series methods if either p(z)/z or q(z)/z2 are not analytic at z = 0. The Frobenius method enables us to create a power series solution to such a differential equation, provided that p(z) and q(z) are themselves analytic at 0 or, being analytic elsewhere, both their limits at 0 exist (and are finite).

## Explanation

The Frobenius method tells us that we can seek a power series solution of the form $u(z)=\sum_{k=0}^\infty A_kz^{k+r}, \qquad (A_0 \neq 0)$

Differentiating: $u'(z)=\sum_{k=0}^\infty (k+r)A_kz^{k+r-1}$ $u''(z)=\sum_{k=0}^\infty (k+r-1)(k+r)A_kz^{k+r-2}$

Substituting: \begin{align} & {} \quad z^2\sum_{k=0}^\infty (k+r-1)(k+r)A_kz^{k+r-2} + zp(z) \sum_{k=0}^\infty (k+r)A_kz^{k+r-1} + q(z)\sum_{k=0}^\infty A_kz^{k+r} \\ & = \sum_{k=0}^\infty (k+r-1) (k+r)A_kz^{k+r} + p(z) \sum_{k=0}^\infty (k+r)A_kz^{k+r} + q(z) \sum_{k=0}^\infty A_kz^{k+r} \\ & = \sum_{k=0}^\infty (k+r-1)(k+r) A_kz^{k+r} + p(z) (k+r) A_kz^{k+r} + q(z) A_kz^{k+r} \\ & = \sum_{k=0}^\infty ((k+r-1)(k+r) + p(z)(k+r) + q(z)) A_kz^{k+r} \\ & = (r(r-1)+p(z)r+q(z))A_0z^r+\sum_{k=1}^\infty ((k+r-1)(k+r)+p(z)(k+r)+q(z))A_kz^{k+r} \end{align}

The expression $r\left(r-1\right) + p\left(0\right)r + q\left(0\right) = I(r) \,$

is known as the indicial polynomial, which is quadratic in r. The general definition of the indicial polynomial is the coefficient of the lowest power of z in the infinite series. In this case it happens to be that this is the rth coefficient but, it is possible for the lowest possible exponent to be r − 2, r − 1 or, something else depending on the given differential equation. This detail is important to keep in mind because one can end up with complicated expressions in the process of synchronizing all the series of the differential equation to start at the same index value which in the above expression is k = 1. However, in solving for the indicial roots attention is focused only on the coefficient of the lowest power of z.

Using this, the general expression of the coefficient of zk + r is $I(k+r)A_k+\sum_{j=0}^{k-1}((j+r)p(k-j)+q(k-j))A_j$

These coefficients must be zero, since they should be solutions of the differential equation, so $I(k+r)A_k+\sum_{j=0}^{k-1}((j+r)p(k-j)+q(k-j))A_j=0$ $\sum_{j=0}^{k-1}((j+r)p(k-j)+q(k-j))A_j=-I(k+r)A_k$ ${1\over-I(k+r)}\sum_{j=0}^{k-1}((j+r)p(k-j)+q(k-j))A_j=A_k$

The series solution with Ak above, $U_{r}(z)=\sum_{k=0}^{\infty}A_kz^{k+r}$

satisfies $z^2U_{r}(z)''+p(z)zU_{r}(z)'+q(z)U_{r}(z)=I(r)z^{r}\!\;$

If we choose one of the roots to the indicial polynomial for r in Ur(z), we gain a solution to the differential equation. If the difference between the roots is not an integer, we get another, linearly independent solution in the other root.

## Example

Let us solve $z^2f''-zf'+(1-z)f=0\,$

Divide throughout by z2 to give $f''-{1\over z}f'+{1-z \over z^2}f=f''-{1\over z}f'+\left({1\over z^2} - {1 \over z}\right) f = 0$

which has the requisite singularity at z = 0.

Use the series solution $f = \sum_{k=0}^\infty A_kz^{k+r}$ $f' = \sum_{k=0}^\infty (k+r)A_kz^{k+r-1}$ $f'' = \sum_{k=0}^\infty (k+r)(k+r-1)A_kz^{k+r-2}$

Now, substituting \begin{align} & \sum_{k=0}^\infty (k+r)(k+r-1) A_kz^{k+r-2} - {1\over z} \sum_{k=0}^\infty (k+r)A_kz^{k+r-1} + \left({1\over z^2} - {1\over z}\right) \sum_{k=0}^\infty A_kz^{k+r} \\ & = \sum_{k=0}^\infty (k+r)(k+r-1) A_kz^{k+r-2} - {1\over z} \sum_{k=0}^\infty (k+r) A_kz^{k+r-1} + {1\over z^2} \sum_{k=0}^\infty A_kz^{k+r} - {1\over z} \sum_{k=0}^\infty A_kz^{k+r} \\ & = \sum_{k=0}^\infty (k+r)(k+r-1)A_kz^{k+r-2}-\sum_{k=0}^\infty (k+r)A_kz^{k+r-2}+\sum_{k=0}^\infty A_kz^{k+r-2}-\sum_{k=0}^\infty A_kz^{k+r-1} \end{align}

We need to shift the final sum. \begin{align} & = \sum_{k=0}^\infty (k+r)(k+r-1) A_kz^{k+r-2} -\sum_{k=0}^\infty (k+r) A_kz^{k+r-2} + \sum_{k=0}^\infty A_kz^{k+r-2} - \sum_{k-1=0}^\infty A_{k-1}z^{k+r-2} \\ & = \sum_{k=0}^\infty (k+r)(k+r-1)A_kz^{k+r-2}-\sum_{k=0}^\infty (k+r)A_kz^{k+r-2}+\sum_{k=0}^\infty A_kz^{k+r-2}-\sum_{k=1}^\infty A_{k-1}z^{k+r-2} \end{align}

We can take one element out of the sums that start with k=0 to obtain the sums starting at the same index. \begin{align} & = ((r)(r-1)A_0z^{r-2})+\sum_{k=1}^\infty (k+r)(k+r-1) A_kz^{k+r-2} - ((r) A_0z^{r-2}) - \sum_{k=1}^\infty (k+r)A_kz^{k+r-2} \\ & {} + (A_0z^{r-2})+\sum_{k=1}^\infty A_kz^{k+r-2}-\sum_{k=1}^\infty A_{k-1}z^{k+r-2} \\ & = (r(r-1)-r+1)A_0z^{r-2} + \sum_{k=1}^\infty \left( ((k+r)(k+r-1)-(k+r)+1)A_k - A_{k-1} \right) z^{k+r-2} \end{align}

We obtain one linearly independent solution by solving the indicial polynomial r(r − 1) − r + 1 = r2 − 2r + 1 = 0 which gives a double root of 1. Using this root, we set the coefficient of zk + r − 2 to be zero (for it to be a solution), which gives us the recurrence $((k+1)(k)-(k+1)+1)A_k - A_{k-1} =(k^2)A_k-A_{k-1}=0\,$ $A_k = {A_{k-1}\over k^2}$

Given some initial conditions, we can either solve the recurrence entirely or obtain a solution in power series form.

Since the ratio of coefficients Ak / Ak − 1 is a rational function, the power series can be written as a generalized hypergeometric series.

## Double roots

The previous example involved an indicial polynomial with a repeated root, which only gave one solution to the given differential equation. In general, the Frobenius method gives two independent solutions provided that the indicial equation's roots are unique.

If the root is repeated, or the roots differ by an integer, then the second solution can be found by the equation: $y_2 = y_1 \ln x + \sum_{k=1}^\infty a_kx^{k+r}$

Where y1(x) is the first solution and the coefficients ak are to be determined.

Wikimedia Foundation. 2010.

### Look at other dictionaries:

• Frobenius — can be*Frobenius Orgelbyggeri, Danish organ building firm*Ferdinand Georg Frobenius (1849 1917), mathematician ** Frobenius algebra ** Frobenius endomorphism ** Frobenius inner product ** Frobenius norm ** Frobenius method ** Frobenius group… …   Wikipedia

• Frobenius solution to the hypergeometric equation — In the following we solve the second order differential equation called the hypergeometric differential equation using Frobenius method, named after Ferdinand Georg Frobenius. This is a method that uses the series solution for a differential… …   Wikipedia

• Frobenius endomorphism — In commutative algebra and field theory, which are branches of mathematics, the Frobenius endomorphism (after Ferdinand Georg Frobenius) is a special endomorphism of rings with prime characteristic p , a class importantly including fields. The… …   Wikipedia

• Ferdinand Georg Frobenius — Infobox Scientist name = PAGENAME box width = image size =150px caption = PAGENAME birth date = October 26, 1849 birth place = Charlottenburg death date = August 3, 1917 death place = Berlin residence = citizenship = nationality = German… …   Wikipedia

• Power series method — In mathematics, the power series method is used to seek a power series solution to certain differential equations. Method Consider the second order linear differential equation: a 2(z)f (z)+a 1(z)f (z)+a 0(z)f(z)=0;!Suppose a 2 is nonzero for all …   Wikipedia

• Perron–Frobenius theorem — In linear algebra, the Perron–Frobenius theorem, proved by Oskar Perron (1907) and Georg Frobenius (1912), asserts that a real square matrix with positive entries has a unique largest real eigenvalue and that the corresponding… …   Wikipedia

• Cartan's equivalence method — In mathematics, Cartan s equivalence method is a technique in differential geometry for determining whether two geometrical structures are the same up to a diffeomorphism. For example, if M and N are two Riemannian manifolds with metrics g and h …   Wikipedia

• List of mathematics articles (F) — NOTOC F F₄ F algebra F coalgebra F distribution F divergence Fσ set F space F test F theory F. and M. Riesz theorem F1 Score Faà di Bruno s formula Face (geometry) Face configuration Face diagonal Facet (mathematics) Facetting… …   Wikipedia

• Ordinary differential equation — In mathematics, an ordinary differential equation (or ODE) is a relation that contains functions of only one independent variable, and one or more of their derivatives with respect to that variable. A simple example is Newton s second law of… …   Wikipedia

• Regular singular point — In mathematics, in the theory of ordinary differential equations in the complex plane , the points of are classified into ordinary points, at which the equation s coefficients are analytic functions, and singular points, at which some coefficient …   Wikipedia